2002
DOI: 10.1517/14728214.7.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein 90 inhibitors as novel cancer chemotherapeutic agents

Abstract: Heat-shock protein 90 (Hsp90) is a molecular chaperone whose association is required for the stability and function of multiple mutated, chimeric and overexpressed signalling proteins that promote cancer cell growth and/or survival. Hsp90 client proteins include mutated p53, Bcr-Abl, Raf-1, Akt, HER2/Neu (ErbB2) and hypoxia inducible factor-1alpha (HIF-1alpha). Through specific interaction with a single molecular target, Hsp90 inhibitors cause the destabilisation and eventual degradation of Hsp90 client protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 71 publications
1
80
0
Order By: Relevance
“…These compounds bind into the ATP binding cleft of the N-terminal domain of Hsp90 preventing the chaperone from cycling between its ADP and ATP-bound conformations (Stebbins et al, 1997;Roe et al, 1999). Both natural products are highly active in preclinical models (Neckers and Neckers, 2002), but, owing to their poor solubility and other pharmacological issues, the clinical evaluation of geldanamycin and radicicol has not been pursued. In the case of geldanamycin, extensive medicinal chemistry efforts have been made to replace the 17-methoxy substituent and generate analogs with improved pharmaceutical properties.…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…These compounds bind into the ATP binding cleft of the N-terminal domain of Hsp90 preventing the chaperone from cycling between its ADP and ATP-bound conformations (Stebbins et al, 1997;Roe et al, 1999). Both natural products are highly active in preclinical models (Neckers and Neckers, 2002), but, owing to their poor solubility and other pharmacological issues, the clinical evaluation of geldanamycin and radicicol has not been pursued. In the case of geldanamycin, extensive medicinal chemistry efforts have been made to replace the 17-methoxy substituent and generate analogs with improved pharmaceutical properties.…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…According to previous studies, the constitutive expression of Hsp90 was found to be 2-10 folds higher in malignant cells compared with normal cells (5). Additionally, several oncogenic proteins are dependent on Hsp90 to function, including B-RAF, protein kinase B (AKT) and extracellular signal-related kinase (ERK) (6). Inhibition of Hsp90 results in the dissociation of corresponding client proteins and induction of apoptosis in cancer cells, and may be accompanied by a reduction in chemotherapy resistance (7).…”
Section: Introductionmentioning
confidence: 97%
“…I n cancer cells, heat-shock protein 90 (Hsp90) interacts in a transformation-specific manner with kinases, hormone receptors, and transcription factors that are directly involved in driving multistep malignancy and also with mutated oncogenic proteins required for the transformed phenotype (1)(2)(3). Association of Hsp90 with client proteins is regulated both by the activity of its N-terminal ATPase domain, which binds and hydrolyses ATP to mediate a series of association-dissociation cycles between Hsp90 and client substrates, and by cochaperones, which modulate the formation of chaperone/client-specific complexes (4).…”
mentioning
confidence: 99%